A Snow Village sketch : Bequest - Manley, William Ford.; Fennelly, Parker; Allen, Arthur; Conway Public Library Collection (Library of Congress) ([New York] : Advertisers Recording Service, 1938)
This radio program takes place in the mythical town of Snow Village. In this episode a man speaks of what he will leave behind after he dies and gives money to a woman who lives alone in the country.
Single-sided, aluminum-based electrical transcription disc.
Part 2 only.
Copies produced by the Library of Congress Magnetic Recording Laboratory were recorded flat, without any equalization curve.
LC copy incomplete: lacks pt. 1.
Production level cataloging.
Written by William Ford Manley.
Keywords: Radio comedies